Effects of banana blossom on breast milk expenditure of mothers during the childbed phase - Nanda, Vina; Santy, Eka; Siswina, Tessa (Borneo Scientific Publishing, 2024)
The postpartum period is a natural phase experienced by women after childbirth and typically lasts approximately six weeks. During this period, various physiological changes occur, including uterine involution, lochia discharge, and the initiation and maintenance of lactation. This study aimed to determine the effect of banana blossom consumption on breast milk production among postpartum mothers at PMB Utin Mulia, Pontianak. A true experimental design with a posttest-only control group approach was employed. The study population consisted of all breastfeeding postpartum mothers in the working area of PMB Utin Mulia. A total of 20 postpartum mothers were selected as samples based on predetermined inclusion criteria. Data were analyzed using the paired t-test. The results demonstrated that banana blossom consumption had a significant effect on breast milk production among postpartum mothers at PMB Utin Mulia. In conclusion, banana blossom consumption was found to influence breast milk production during the postpartum period.